values Of Multicultural Islamic Education: Interaction Between Students And The Chinese Community In Lasem - Sholihuddin, Moh; Shobirin, Muhammad (The Islamic Education and Multiculturalism Foundation, 2024)
Abstract: The multicultural insight possessed by citizens is a concrete example of how differences do not always trigger divisions or rifts, but can still live in harmony according to what is taught in Islam as well as the values of Pancasila and global development. In the field, there are many intolerance issues that occur, the objectives of this research are 1. Explain how to inculcate the values of multicultural Islamic education in the interaction of students with the Chinese community in Lasem. 2. Analyze the Islamic values of multicultural Islamic educators found in the interaction of students with the Chinese community in Lasem. The research method used is field research. In this study, researchers use a qualitative approach to describe and analyze events, social activities, phenomena, attitudes, perceptions, beliefs, and individual thoughts. In addition, qualitative research is usually in charge of describing and investigating and describing and explaining. In this study, seven multicultural Islamic values were obtained based on the process of observation, interviews, and documentation. The seven multicultural values are: mutual cooperation, friendliness and manners, caring for the surroundings, accepting differences or pluralism, harmony and peace, non-violence, and being adaptive to culture. Based on the discussion, it can be concluded that there are seven multicultural Islamic values consisting of mutual cooperation, friendliness and manners, caring for the surroundings, accepting differences or pluralism, harmony and peace, non-violence, and being adaptive to culture. The inculturation of multicultural Islamic values in students is embedded in various ways, in this case obtained from education inside the cottage and from outside the cottage. Among them are: (1) the model of exemplary kiyahi, (2) the model of adaptation, (3) the model of habituation, and (4) and the model of symbolic interaction in the Lasem community.